In Situ Imaging of Electrode Thickness Growth and Electrolyte Depletion in Single-Crystal vs Polycrystalline LiNixMnyCozO2/Graphite Pouch Cells using Multi-Scale Computed Tomography. Issue 2 (1st February 2022) - Bond, Toby; Gauthier, Roby; Eldesoky, A.; Harlow, Jessie; Dahn, J. R.
Abstract : Single-crystal LiNix Mny Coz O2 (NMC) materials have recently garnered significant academic and commercial interest as they have been shown to provide exceptional long-term charge-discharge cycling stability in Li-ion cells. Understanding the degradation mechanisms occurring in conventional polycrystalline NMC materials in comparison to the more stable single-crystal equivalents has become a topic of great importance. In this study, we demonstrate how multi-scale, in situ computed tomography can be used to characterize important changes occurring in wound pouch cells containing polycrystalline vs single-crystal NMC. These changes include cell-level phenomena (such as deformation of the jelly roll and electrolyte depletion) as well as electrode-scale phenomena (such as electrode thickness growth and electrode cracking). Twenty-one cells were scanned in total, consisting of three different electrodes: polycrystalline NMC622, single-crystal NMC811, and single-crystal NMC532. These cell matrices were designed to characterize the effects of varying C-rate, depth of discharge, and duty cycle. This work includes a comprehensive analysis of these factors as they relate to physical changes taking place at both the cell and electrode level.